Learning wireless Java - Mahmoud, Qusay H., 1971- (O'Reilly, 2002)
Learning Wireless Java is for Java developers who want to quickly come up to speed and create applications for the Micro Edition audience. This book covers the Connected, Limited Device Configuration and the Mobile Information Device Profile (MIDP), both currently available from Javasoft. The CLDC contains APIs for small devices that are constrained by both memory and processing power. MIDP builds on top of the CLDC and adds APIs specifically for devices such as mobile phones and pagers, allowing programmers to create MIDlet applications. This book offers a solid introduction to J2ME and MIDP, including an explanation of the J2ME Wireless Toolkit, the MIDlet lifecycle methods, the Java application manager, and the CLDC and MIDP constraints. In addition, we cover the javax.microedition.io, javax.microedition.rms, javax.microedition.lcdui, and javax.microedition.midlet classes, as well as the modified java.lang, java.io, and java.util classes. Discussion centers around building safe, compact applications with the sophisticated graphical interface, database, and networking capabilities that the J2ME supports. In addition, this book also shows you how to download your applications to the latest J2ME-enabled devices, including the Motorola i50x and i85s phones and upgraded Palm handhelds.